‘The many-layered palimpsest: metafiction, genre fiction, and Georges Perec’s “53 jours”’ - Kemp, S (Cambridge Scholars Publishing, 2014)
French Crime Fiction and the Palimpsest Angela Kimyongür, Amy Wigelsworth. Rewriting Wrongs: French Crime Fiction and the Palimpsest. 201 Dora Bruder, 146 Monteilhet, Hubert Le Retour des cendres, 19 multidirectional memory, 18, 32, ...